Malawi Economic Monitor, May 2018 : Realizing Safety Nets' Potential - World Bank (Lilongwe, World Bank, 2018)
This Malawi Economic Monitor (MEM) provides an analysis of economic and structural development issues in Malawi. The aim of the publication is to foster better-informed policy analysis and debate regarding the key challenges that Malawi faces in its endeavor to achieve high rates of stable, inclusive and sustainable economic growth. The MEM consists of two parts: Part 1 presents a review of recent economic developments and a macroeconomic outlook. Part 2 focuses on a special selected topic relevant to Malawi’s development prospects. In this edition, the special topic focuses on Social Safety Nets. Safety nets are playing an increasing role in promoting equity, strengthening resilience, and improving long-term human capital outcomes. There is now robust evidence to demonstrate that social safety nets can be an efficient means to break the cycle of poverty and vulnerability in Malawi. The key messages of this edition of the MEM are about economic recovery and cautious optimism.